2012
DOI: 10.1002/hfm.20535
|View full text |Cite
|
Sign up to set email alerts
|

Application of Digital Manuals with a Retinal Imaging Display in Manufacturing: Behavioral, Physiological, and Psychological Effects on Workers

Abstract: This study analyses the behavioral, physiological, and psychological effects of digital manuals presented by a retinal imaging display (RID) on workers in the manufacturing industry. An RID consists of wearable glasses that enable users to view a digital image overlaying the real world. We conducted an experiment in which subjects assembled an object by referring to different types of manuals. The experimental results suggest that an RID enables users to conveniently examine real objects against information in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Nakanishi and Sato (2015) evaluated the psychological and physiological effect of digital manuals presented by a retinal imaging display on workers in the manufacturing industry. Rapaccini et al (2014) provided the results of a field study of user acceptance of AR to support the delivery of field services (e.g., maintenance activities) on installed products, and Olsson et al (2012) carried out a similar study to evaluate the user acceptance, potentials and risks associated to five different mobile AR scenarios.…”
Section: Conceptual Papersmentioning
confidence: 99%
“…Nakanishi and Sato (2015) evaluated the psychological and physiological effect of digital manuals presented by a retinal imaging display on workers in the manufacturing industry. Rapaccini et al (2014) provided the results of a field study of user acceptance of AR to support the delivery of field services (e.g., maintenance activities) on installed products, and Olsson et al (2012) carried out a similar study to evaluate the user acceptance, potentials and risks associated to five different mobile AR scenarios.…”
Section: Conceptual Papersmentioning
confidence: 99%
“…In the same study, workers using AI and other smart technology experience separation anxiety when away from devices (Meissner et al, 2020). Studies on the use of extended reality technologies (VR/AR) and smart wearables in the working context, indicate risks of information-processing overload, problem-solving difficulties and cognitive overload leading to operation errors (Chao et al, 2017;Marques et al, 2022;Nakanishi and Sato, 2015). Moreover, Brougham and Haar (2018) showed that workers show higher levels of job insecurity and lower levels of job satisfaction and organizational commitment (i.e., psychological engagement and dedication to their work) when they are aware of technological changes occurring in their workplace.…”
Section: Ejimmentioning
confidence: 90%
“…Several authors have concentrated on cognitive theories as framework to evaluate cognitive load in the interaction with technology (Chao et al, 2017). Nakanishi and Sato (2015) referred to information-processing theory (IPT) to focus on the employee's cognitive capacity. In their study, they evaluated the behavioral, physiological and psychological effects on workers in application of digital manuals with a retinal imaging display in manufacturing.…”
Section: Risks and Digital Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakanishi and Sato 31 analyzed heart activity by Electrocardiogram (ECG) and brain blood flow in the right and left cerebral hemispheres by near infrared spectroscopy (NIRS) during an assembly task. The objective was to assess the stress digital manuals presented by a retinal imaging display (RID) on workers in the manufacturing industry.…”
Section: Affective Computing In Manufacturingmentioning
confidence: 99%